2016
DOI: 10.1590/1678-4324-2016150529
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effect on Cancerous Cell Lines by Biologically Synthesized Silver Nanoparticles

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 13 publications
5
19
0
Order By: Relevance
“…The peak at around 1630 cm −1 was representative of crystalline β‐sheet structures, which was in accordance with previous findings on native sericin structure . Amide I representing absorption bands in the region 1630 and 1660 cm −1 were suggestive of additional amorphous random coil structures . For rice starch, all characteristic bands mentioned by Kizil et al were observed .…”
Section: Resultssupporting
confidence: 90%
“…The peak at around 1630 cm −1 was representative of crystalline β‐sheet structures, which was in accordance with previous findings on native sericin structure . Amide I representing absorption bands in the region 1630 and 1660 cm −1 were suggestive of additional amorphous random coil structures . For rice starch, all characteristic bands mentioned by Kizil et al were observed .…”
Section: Resultssupporting
confidence: 90%
“…And svLAAO induced proapoptotic genes up regulation and down regulation of anti apoptotic genes in a significant way compared with nontreated cells in addition it induced different cellular arrest at G0/G1 phase. In the mean times evaluation of anticancer activity of Ag NPs and its antimicrobial activity , data recorded was in agreement with (Kulandaivelu et al, 2016) demonstrated thatthe cytotoxic effects of the silver nanoparticles could significantly inhibited MCF7 cancer cell line proliferation in a time and concentration-dependent manner by MTT assay. This result is much closed to our result.…”
Section: Resultssupporting
confidence: 85%
“…At 100μg/ mL concentration, the silver nano-particles exhibited significant cytotoxic effects and the apoptotic features were confirmed through caspase-3 activation and DNA fragmentation assays [6]. Silver AgNPs were produced by reduction of Silver Nitrate by using aqueous of fresh aerial parts of Alternanthera Sessilie.…”
Section: Qaysar Mohi Ud Din Biomed J Sci and Tech Res Volume 1-issue 4mentioning
confidence: 92%
“…In most of the cases reducing agents or other constituents present in the cells acts as stabilizing and capping agents, so there is no need of adding capping and stabilizing agents from outside [4]. The Ag+ ions are primary requirement for the synthesis of AgNPs which can be obtained from various water soluble salts of silver [5].…”
Section: Green Synthesis Of Npmentioning
confidence: 99%